1979
DOI: 10.1128/aac.16.6.869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cefamandole nafate on blood coagulation and platelet function

Abstract: Platelet function and coagulation were tested after brief in vivo exposure to cefamandole nafate and in the presence of various concentrations of the drug in vitro. Alterations in hemostatic function were observed only with exposure to drug concentrations severalfold higher than those expected to prevail clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Previous clinical evaluations of ceftazidime have been reported in the therapy of varied infections in a few patients each (3,6,22,23). Although ceftazidime would not be considered a first-line drug for the therapy of community-acquired pneumonia, a clinical trial was designed to compare the efficacy and safety of ceftazidime to cefamandole in the treatment of such pneumonias, with particular attention directed toward secondary coagulation abnormalities (1,4,7,31) and the development of resistance during therapy (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Previous clinical evaluations of ceftazidime have been reported in the therapy of varied infections in a few patients each (3,6,22,23). Although ceftazidime would not be considered a first-line drug for the therapy of community-acquired pneumonia, a clinical trial was designed to compare the efficacy and safety of ceftazidime to cefamandole in the treatment of such pneumonias, with particular attention directed toward secondary coagulation abnormalities (1,4,7,31) and the development of resistance during therapy (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…The impact that therapeutic antibacterials have upon the coagulation profile has been previously described, albeit largely in patients without hematologic malignancies. Prolongation of both the PT and PTT is shown to occur in a dose and time-dependent manner [16]. One study demonstrated that as few as seven consecutive days of intravenous cephalosporin administration can prolong the PT, although this did not translate into a higher rate of bleeding [17].…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION Antibiotic-induced platelet dysfunction has been reported most frequently with carbenicillin and penicillin (2,4). However, other penicillins and some cephalosporins, including a few of the newer agents (e.g., piperacillin and moxalactam), have been shown to produce platelet dys- function at various concentrations (3,6,8,13,14). The cases presented here suggest that nafcillin can also induce a hemostatic defect attributable to platelet dysfunction.…”
mentioning
confidence: 88%